Neuroethical issues in adopting brain imaging for personalized chronic pain management: Attitudes of people with lived experience of chronic pain - Karen Deborah Davis; Monica de Oliveira; Ariana Besik; Daniel Z. Buchman (Canadian Journal of Pain)
Background Pain is an individual and subjective experience that places a burden on individuals to convince others they have pain. Brain imaging technologies can potentially inform pain management but raise neuroethical questions.Aims We examined the degree of endorsement and concerns of adults in Canada with chronic pain regarding the use of brain imaging to detect and treat chronic pain in six areas: new brain imaging technologies, brain data privacy, stigma, treatment, objective representations of pain, and dismissing pain self-reports.Results An online survey was completed by 349 Canadian adults living with chronic pain. Most respondents were open to using brain imaging for diagnostics, prediction, and therapeutic decision making (>90%). More than half of respondents felt that a brain scan would give them more confidence in their diagnosis and treatment plans and that health care providers would be more likely to believe they had chronic pain. However, they worried that brain scans could be used to dismiss their pain self-report. Most respondents felt there were policies to protect their brain data, but 40% were concerned about privacy and brain scan use against them by their employers/insurers. Although most respondents felt that a brain scan could represent their pain and suffering, 80% disagreed that their pain is only real if seen in a brain scan.Conclusions People with chronic pain recognize the potential benefits of brain imaging but are concerned about data security and dismissal of their self-reported pain. Our data align with previous recommendations to use brain imaging as an adjunct to pain self-reports but not as a replacement for the same.